2016
DOI: 10.1055/s-0042-109170
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of platelet-rich plasma as a shielding technique after endoscopic mucosal resection in rat and porcine models

Abstract: Background and study aims: The aims were to assess the efficacy of endoscopic application of Platelet-rich plasma (PRP) to prevent delayed perforation and to induce mucosal healing after endoscopic resections. Patients and methods: Colonic induced lesions were performed in rats (n = 16) and pigs (n = 4). Animals were randomized to receive onto the lesions saline (control) or PRP. Animals underwent endoscopic follow-up. Thermal injury was assessed with a 1 – 4 scale: (1) mucosal necrosis; (2) submucosal necrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Such evidence would be useful for the treatment of large artificial ulcers or artificial ulcers in the lower third of the stomach. Shielding using platelet rich plasma (PRP) has also been shown to be effective in significantly reducing the size of EMR-induced ulcers of the colon in both rats and pigs (2.4% reduction in the control group versus 80% in treated animals) [27]. However, to our knowledge, there are no clinical reports on the use of PRP for the treatment of ulcers post-ESD.…”
Section: Discussionmentioning
confidence: 99%
“…Such evidence would be useful for the treatment of large artificial ulcers or artificial ulcers in the lower third of the stomach. Shielding using platelet rich plasma (PRP) has also been shown to be effective in significantly reducing the size of EMR-induced ulcers of the colon in both rats and pigs (2.4% reduction in the control group versus 80% in treated animals) [27]. However, to our knowledge, there are no clinical reports on the use of PRP for the treatment of ulcers post-ESD.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, sealing mucosal lesions with endoscopic applied chitosan hydrogel containing epidermal growth factor induced both, a significant reduction in mucosal resection‐induced gastric ulcers in rabbits and pigs, and the appearance of deep scar formation and fibrotic submucosa in untreated lesions . More recently, our group has assessed the utility of platelet‐rich plasma applied onto colonic‐induced lesions, showing strong healing properties in preclinical studies …”
Section: Discussionmentioning
confidence: 99%
“…Until now, we do not have any valid endoscopic treatment to prevent this delayed complication; therefore, new methods are needed. In this sense, our group has proposed that endoscopic shielding technique (EndoSTech) is a new and easy way to manage lesions resulting from therapeutic endoscopy . As an important unmet topic in this field, we have developed a new topical composition, applied as a shield, to prevent CS.…”
Section: Introductionmentioning
confidence: 99%
“…The rationale for use PRP as solution to perform submucosal injection in endoscopic resection techniques lies in the exponential release of multiple bioactive factors, and subsequently, enhances the natural healing process, as well as in its haemostatic properties, with very low risk of fibrotic healing or strictures. In gastrointestinal disorders PRP has demonstrated efficacy in the prevention of DP[ 7 ] and wound healing in primary colonic anastomosis[ 12 ]. Previous reports have confirmed that surgical sites enhanced with PRP heal at rates two to three times those of untreated surgical sites and anabolic effects are directly correlated to platelet number[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The optimal fluid to lift the lesion is still a matter of debate. Platelet-rich plasma (PRP), as autologous concentrated in plasma, has demonstrated strong healing properties as a shield over the eschars after EMR in preclinical models[ 6 , 7 ]. PRP solution has showed the best electrical and rheological properties to perform safety endoscopic resections[ 8 ].…”
Section: Introductionmentioning
confidence: 99%